Estimation of Heterosis in Newly Evolved CSR Bivoltine Hybrids of Silkworm (Bombyx mori L.) at Room and High Temperature - Verma, Gurvinder Raj; Sajgotra, Mokshe (International Journal of Bio-resource and Stress Management, 2023)
Silkworm breeds/hybrids which are reared over a series of environment exhibiting less variation are considered stable. Identification of high temperature tolerant bivoltine breeds/hybrids by screening for thermo tolerance in silkworm is an essential prerequisite for the development of thermo-tolerant bivoltine breeds/hybrids. One of the main aims of the breeders is to recommend breeds/hybrids that are stable under different environmental conditions and minimize the risk of falling below a certain yield level to farmers. In the present study, an attempt was made to evaluate and identify thermo-tolerant, adaptable bi×bivoltine silkworm hybrids suitable for rearing throughout the year, raised by involving seven productive breeds (CSR2, CSR3, CSR4, CSR5, CSR6, KA and NB4D2) and two thermo-tolerant breeds (CSR18 and CSR19) at two different temperature regime (25±1 °C and 36±1 °C ). The data was subjected to the estimation of heterosis in relation to mid parent value and heterobeltiosis in relation to better parent value. Observations made for four economically important traits namely; pupation percentage, single cocoon weight, single shell weight and shell ratio percentage revealed that at 25±1 °C (optimum environmental conditions) productive hybrid CSR3×CSR6 (heterosis over mid parent value (66.99) and heterobeltiosis over better parent value (50.62) results in better qualitative and quantitative traits as compared to other hybrids studied. Robust hybrid, CSR18×CSR19 showed better tolerance to high temperature i.e. at 36±1 °C and recorded heterosis for mid parent value of 55.03 and heterobeltiosis for better parent value of 32.40 when compared to productive hybrids.